2021
DOI: 10.1039/d0ob02428g
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological evaluation of a halogenated phenazine-erythromycin conjugate prodrug for antibacterial applications

Abstract: We report the synthesis and initial biological assessment of a halogenated phenazine–erythromycin conjugate prodrug 5 aimed to treat bacterial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…By comparison, previous studies which focused solely on bacterial resistance to the parent form of antibiotics yielded parameters that may not apply to prodrug forms. For example, the minimum inhibitory concentration (MIC) is commonly used as a parameter for resistance (Brauner et al , 2016 ), yet the MIC of the parent and pro‐forms of the same drug can differ, as seen with both model prodrugs used in this study as well as others from the literature (Wang et al , 2018 ; Evans et al , 2019 ; Yang et al , 2021 ). Using existing MIC classifications, these prodrugs could have been labeled ineffective; yet, our experiments showed that different environmental conditions or, in the case of AMP prodrugs, linker sequences, may result in success.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…By comparison, previous studies which focused solely on bacterial resistance to the parent form of antibiotics yielded parameters that may not apply to prodrug forms. For example, the minimum inhibitory concentration (MIC) is commonly used as a parameter for resistance (Brauner et al , 2016 ), yet the MIC of the parent and pro‐forms of the same drug can differ, as seen with both model prodrugs used in this study as well as others from the literature (Wang et al , 2018 ; Evans et al , 2019 ; Yang et al , 2021 ). Using existing MIC classifications, these prodrugs could have been labeled ineffective; yet, our experiments showed that different environmental conditions or, in the case of AMP prodrugs, linker sequences, may result in success.…”
Section: Discussionmentioning
confidence: 96%
“…For example, agent‐based simulations revealed that the rate of prodrug activation (i.e., catalytic efficiency, k cat / K M ) had a strong effect on the MIC of each compound (Murphy et al , 2011 ). Furthermore, empirical studies have found there to be differences in MIC between parent and prodrug forms, as well as higher variance in prodrug MIC across bacterial strains, relative to the parent drug (Wang et al , 2018 ; Evans et al , 2019 ; Yang et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…12 Phenazine derivatives 4-6 displayed antiviral activity against bovine viral diarrhea virus (Figure 1). 13 Moreover, phenazine scaffold is also used in other research fields, for example, its conjugation with erythromycin as a prodrug for antibacterial applications, 14 and being used in biosensor and materials. 15,16…”
Section: Antiviral Alkaloids and Alkaloid-like Compounds From Commonl...mentioning
confidence: 99%
“…Structure of a drug ceftazidime (13), an inhibitor of viral spike protein-ACE2 interaction GRL0617 ( 14) is an antiviral drug lead, and it was found to be a noncovalent class of papain-like protease (PLpro) inhibitor of SARS-CoV virus (Figure 4). 21 Among the library of 50,080 compounds, GRL0617 (14) was found to be the most potent PLpro inhibitor, and it was co-recrystallized with the enzyme PLpro.…”
Section: Figure 1 Antiviral Phenazine Derivatives 1-6mentioning
confidence: 99%
“…Here, antimicrobials can be linked to antibodies, peptides, or various compounds to improve (i) target specificity, (ii) penetration of the biofilm matrix, or (iii) condition-specific activity [ 162 , 163 , 164 , 165 , 166 , 167 , 168 ]. This approach can reduce the efficacy of biofilms’ protective and resistant nature when challenged by traditional antibiotics and has found success in recent studies and clinical trials [ 169 , 170 , 171 ].…”
Section: Therapeutic Drug Conjugatesmentioning
confidence: 99%